2013
DOI: 10.1016/j.ultsonch.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Sono-thermal pre-treatment of waste activated sludge before anaerobic digestion

Abstract: Sonication and thermalization can be applied successfully to disrupt the complex waste activated sludge (WAS) floc structure and to release extra and intra cellular polymeric substances into soluble phase along with solubilization of particulate organic matters, before sludge digestion. In this study, sonication has been combined with thermalization to improve its disintegration efficiency. It was aimed that rise in temperature occurring during the sonication of sludge was used to be as an advantage for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 26 publications
2
33
2
2
Order By: Relevance
“…To facilitate the sludge liquefaction, various sole and combined disintegration methods (e.g., thermal, thermochemical, ultrasonic, microwave, and biological disintegrations) have been applied to pretreat Waste activated sludge (WAS), as reported in the literature (Uma et al, 2012a;Gayathri et al, 2015;Ebenezer et al, 2015;Kavitha et al, 2013Kavitha et al, , 2015b. Several researchers have reported affirmative synergistic upshots of the combined pretreatment methods on subsequent anaerobic digestibility (Tyagi and Lo, 2012;Zhen et al, 2014;Sahinkaya and Sevimli, 2013). Among the combinative pretreatment methods, thermochemical was widely applied to disintegrate the sludge (Tyagi and Lo, 2012;Sahinkaya and Sevimli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the sludge liquefaction, various sole and combined disintegration methods (e.g., thermal, thermochemical, ultrasonic, microwave, and biological disintegrations) have been applied to pretreat Waste activated sludge (WAS), as reported in the literature (Uma et al, 2012a;Gayathri et al, 2015;Ebenezer et al, 2015;Kavitha et al, 2013Kavitha et al, , 2015b. Several researchers have reported affirmative synergistic upshots of the combined pretreatment methods on subsequent anaerobic digestibility (Tyagi and Lo, 2012;Zhen et al, 2014;Sahinkaya and Sevimli, 2013). Among the combinative pretreatment methods, thermochemical was widely applied to disintegrate the sludge (Tyagi and Lo, 2012;Sahinkaya and Sevimli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Surplus sludge produced by various treatment plants are of an immense ecological peril due to the presence of unprocessed solids, pathogens and other organic pollutants (Sahinkaya and Sevimli, 2013;Kavitha et al, 2013 Conversely, the management of sludge is one of the most tedious and costly processes in the treatment plants. The treatment and disposal of these unprocessed sludge accounts up to 60% of the total functioning cost of the wastewater treatment plants (WWTPs) (Appels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The sludge flocs were rapidly disrupted and the exposed cells were disintegrated in the rapid sludge disintegration stage, while additional cells were exposed and damaged by sonication in the following slow disintegration stage (Huan et al, 2009). Similarly, Huan et al (2009), Şahinkaya and Sevimli (2013a), Yan et al (2010) and Zhang et al (2007) also reported that the ultrasonic sludge disintegration occurred in two stages. The reason for this rapid disintegration obtained in the first 10 min was the rapid cavitational effect arising from the collapse of powerful transient bubbles created in fractions of microseconds close to microbial cells (Show et al, 2007).…”
Section: Effect Of Sonication On Sludge Disintegrationmentioning
confidence: 93%
“…Inevitably, the formation of large amounts of excess biomass (called "waste activated sludge, WAS") is the most important disadvantage of the activated sludge process. Prior to final disposal of the WAS, it must be treated, because its improper disposal brings about a significant threat for ecological systems due to its highly putrescible nature and its pathogen content (Şahinkaya and Sevimli, 2013a). However, the treatment and disposal of the waste sludge are among the most difficult and expensive problems in the treatment plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation